Asymmetric incentives and the new politics of monetary policy. (7th November 2020) - Park, Gene; Cheung, Gabrielle; Katada, Saori N
Abstract: This article develops and tests a theory of asymmetric incentives to explain why politicians might be less motivated to confront deflation than inflation. Leveraging Japan as a least-likely crucial case, we analyze the conditions that lead legislators to take advantage of their power to summon central bankers for questioning. We find that even moderate inflation makes it more likely that legislators will summon central bankers compared to periods when the inflation rate is near zero. By contrast, deflation has either no effect or reduces the likelihood of summonses. We also find some evidence that unconventional monetary policies to combat deflation, specifically quantitative easing, are likely to invite greater legislative scrutiny. These findings have important policy implications. While deflation is widely viewed as pernicious and more difficult to exit than inflation, there are weaker incentives for politicians to address it.